Designing TED-TI instructional strategy: tackling high-density classroom management dilemmas and tapping into the employment potential of native-language public speaking education - Zheng, Xiaojian; Mohd Puad, Mohd Hazwan; Ab. Jalil, Habibah; Wang, Wei (Taylor and Francis, 2025)
Given the profound impact of Technology, Entertainment, Design (TED) Talks and Toastmasters International (TI) on Public Speaking Competency (PSC), this study aimed to integrate them into the local non-English speaking tertiary vocational education system. Concomitantly, under-recognized mother-tongue PSC education also confronts the challenge of managing densely populated classrooms. This study designed a TED-TI classroom instructional strategy and developed employment-oriented mother-tongue PSC courses using the ADDIE design model. In the analysis stage, design motivation of the capacity rebuilding and pedagogy demands is clarified; in the design stage, a TED-TI classroom teaching model is created; in the development stage, mother-tongue PSC and employment elements are integrated to produce auxiliary textbooks, TED Thinking Taskbook and TI Meeting-style Training Booklet; in the implementation and evaluation stage, TED-TI is optimized through internal design validation. These promising pilot results suggest the potential for expanding TED-TI, including larger-scale applications, extending beyond Mandarin, further investigating local employment promotion schemes via PSC, and aiding countries in grappling with educational equity challenges.